2022
DOI: 10.31557/apjcp.2022.23.10.3387
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MRI as Non-Invasive Diagnostic Tool for Rectal Cancer Aggressiveness and Correlation with KI-67 Expression in Tumor Tissue

Abstract: Background and aim: Apparent diffusion coefficient (ADC) was suggested as a prognostic marker in rectal carcinoma (RC). However, reported data are inconsistent. The present study aimed to assess the relation between ADC value and Ki-67 expression index and other pathological parameters in Egyptian RC patients. Materials and Methods:The study included 39 patients with newly diagnosed RC (non-mucinous adenocarcinoma). All patients underwent magnetic resonance imaging (MRI) scan by 1.5T magnet. Mean ADC value was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Tumor composition and characteristics can be used to assess physiological and pathological processes or pharmacological responses to therapeutic interventions. A previous study found that the apparent diffusion coefficient (ADC) derived from diffusion-weighted imaging (DWI) had a significant inverse correlation with Ki-67 ( 7 ). Multi-parametric breast MRI correlated with the stroma component of invasive breast cancer ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor composition and characteristics can be used to assess physiological and pathological processes or pharmacological responses to therapeutic interventions. A previous study found that the apparent diffusion coefficient (ADC) derived from diffusion-weighted imaging (DWI) had a significant inverse correlation with Ki-67 ( 7 ). Multi-parametric breast MRI correlated with the stroma component of invasive breast cancer ( 8 ).…”
Section: Introductionmentioning
confidence: 99%